An anti-pressure, fatigue-resistant and rapid self-healing hydrogel based on a nano-micelle assembly. Issue 13 (10th March 2020) - Shao, Zhiang; Cheng, Weimin; Hu, Xiangming; Zhao, Yanyun; Wang, Peng; Wu, Mingyue; Xue, Di; Hou, Jiaoyun; Bian, Susu
Abstract : A trace amount of acetic acid can cause DMC-NaSS micelles to split, resulting in the formation of a novel self-healing hydrogel. Abstract : Herein, we found that a trace amount of acetic acid can strengthen DMC-NaSS micelles, resulting in a novel self-healing hydrogel with multiple non-covalent crosslinks. The hydrogel has both excellent self-healing capabilities and mechanical properties.